Sex blind: bridging the gap between drug exposure and sex-related gene expression in Danio rerio using next-generation sequencing (NGS) data and a literature review to find the missing links in pharmaceutical and environmental toxicology studies - King, Alex C.; Zenker, Armin K. (Frontiers in Toxicology, 2023)
The gender of both humans and Danio rerio has previously been shown to affect the way individuals respond to drug exposure. Genes which allow identification of sex in juvenile zebrafish show potential to reveal these cofounding variables between gender in toxicological and preclinical trials but the link between these is so far missing. These gender-specific, early-expressed genes where expression is not altered by drug exposure must be carefully selected for this purpose. We aimed to discover genes which can be used in pharmaceutical trials and environmental toxicology studies to uncover sex-related variations in gene expression with drug application using the model organism Danio rerio. Previously published early sex-determining genes from King et al. were evaluated and additional genes selected which are less susceptible to drug exposure. Using our NGS data from zebrafish, we revealed a further ten female-specific genes (vtg1, cyp17a1, cyp19a1a, igf3, ftz-f1, gdf9, foxl2a, Nr0b1, ipo4, lhcgr) and five male-related candidate genes (FKBP5, apobb1, hbaa1, dmrt1, spata6) which are also expressed in juvenile zebrafish, 28dpf. Previous studies were used to classify these genes to highlight the effect of their expression with drug exposure in order to determine the best genes to be used in pharmaceutical trials or environmental toxicology studies. Discovery of these early sex-determining genes in Danio rerio will allow identification of gender-related responses to drug testing to improve sex-specific healthcare and the medical treatment of human patients.